NEEDS ANALYSIS OF LECTURER AND EMPLOYEE TRAINING PROGRAM AT TARBIYAH AND TEACHER TRAINING FACULTY OF UIN ALAUDDIN MAKASSAR - Idris, Ridwan; Nursita, Lisa (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to investigate lecturers’ and employee’ competencies of Tarbiyah and Teacher Training Faculty at UIN Alauddin Makassar and assess the training program needs for 2023–2024. The research method used was quantitative descriptive with survey techniques. The population was the lecturers and employees of Tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar, consisting of 113 lecturers and 35 employees. The instruments used were Likert scale questionnaires and documentation from the Quality Assurance Commission of Tarbiyah dan Teacher Training Faculty. The results of the study indicated that various training programs were attended by lecturers and employees held by UIN Alauddin Makassar and other agencies. The training needs for lecturers are adjusted to the competencies that must be possessed, namely pedagogical, professional, and social, as well as the implementation of the tri dharma of higher education. Employee training should focus on increasing knowledge and skills according to job descriptions. Abstrak: Penelitian ini bertujuan untuk mengetahui kompetensi dosen dan pegawai Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar serta mengkaji kebutuhan program pelatihan tahun 2023–2024. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan teknik survey. Populasi penelitian ini adalah dosen dan pegawai Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar yang terdiri dari 113 dosen dan 35 pegawai. Instrumen yang digunakan adalah angket skala Likert dan dokumentasi dari Komite Penjaminan Mutu (KPM) Fakultas Tarbiyah dan Keguruan. Hasil penelitian menemukan bahwa berbagai program pelatihan diikuti oleh dosen dan pegawai yang diadakan oleh UIN Alauddin Makassar dan instansi lainnya. Kebutuhan pelatihan bagi dosen disesuaikan dengan kompetensi yang harus dimiliki yaitu pedagogik, profesional, dan sosial, serta pelaksanaan tri dharma perguruan tinggi. Pelatihan karyawan harus fokus pada peningkatan pengetahuan dan keterampilan sesuai dengan deskripsi pekerjaan.